Creation and development of a Permanent Health Education Observatory of Ceará (Research, Society and Development, 2021)
Objective: to develop the stages of creation and implementation of the Observatory of Permanent Health Education in Ceará. Methodology: a methodological study was carried out. For this study, the first stage of a methodological study (construction stage) was used. Results: the information that includes the results regarding the creation and implementation of the Observatory are described through thematic categories: (1) Prototype Ideation; (2) Health Information Mining; (3) The website. In category indicators were created, which are: data from profession councils; institutions that were; number of continuing education in health; maps of health residences in Ceará; SUS management data in Ceará; Ceará Municipal Health Councils; and Hospital Studies Centers. Final considerations: with the creation and development of the Observatory, it is believed that the experiences of teaching-service-community integration are of great relevance, not only for the Observatory, but for the valuation and development of Permanent Health Education practices in Ceará. , strengthening and disseminating what was previously only present in a certain field so that it can favor innovation and growth in this area.